The US withdrawal from the Paris climate agreement: What lies ahead and who fills the vacuum? - Kumar, Sameer (AEI Insights, 2021)
Today, the US pulled out of the Paris Climate Agreement, citing that it would undermine its economy, take away jobs, pose litigation risks, and put the US in a permanent disadvantageous position vis-a-vis other countries. By doing so, President Trump was fulfilling his election promise to support the nation’s coal industry, and had the Trump administration not exited the accord, it would have come into imminent direct conflict with the promise he made to the people during the campaign. Hence, the exit was expected.